COLLECTION OF SANDFLY LARVAE FROM RODENT BURROWS - E. Javadian; A. Nadim; A. Mesghali (Tehran University of Medical Sciences, 1974)
During a search of burrows for the purpose of capturing rodents in 1972, a number of soil samples were inspected for the collection of sand fly larvae. In this study, a total of 472 plastic bags of soil samples were collected from different depths of 30 rodent burrows. Fourteen of these samples were found positive, from which 27 larvae were removed. Most of the larvae were found in the depths of the burrows and in rodent food reservoirs. The result of this survey shows that rodent burrows are the most suitable breeding places for sand fly larvae in the Ahwaz area.